Self-Reported Antibiotics Usage, Allergies and Resistance of Albanian Patients from a Dental Perspective: A Preliminary Questionnaire-Based Survey - Blerina Zeza; Nisrina Kraja; Valbona Disha; Erdita Cenameri; Esat Bardhoshi (MDPI AG, 2024)
Objectives: The paper aims to assess the level of antibiotic use and the antibiotic types used generally in dentistry and identify self-reported allergies and resistance related to them. Methods: The data were collected between March and May 2024 via an electronic questionnaire on self-reported antibiotic usage, antibiotic allergies and resistances among individual in Albania. Results: A total of 477 individuals (83% females, 17% males) with a mean 33 ± 13 (min 17; max 73) years of age completed the questionnaire. Overall, 88% of the population reported having used antibiotics before the questionnaire, among whom 56% used them for dental reasons. An average of 5% reported being allergic, mainly to the penicillin group, while 5% claimed to have undergone an antibiogram analysis before taking the prescribed antibiotics, with most of them showing resistance to the penicillin group. Conclusions: Based on the findings of this study, the high prevalence of antibiotics usage in dentistry encourages further deepening studies and training adapting global guidelines for antibiotics indications in dentistry to the level of antibiotics allergies and resistances of this specific country.